Exploration of women's decision-making process to abort or continue an unintended pregnancy: A grounded theory study - Roghaiyeh Nourizadeh; Eesa Mohammadi; Masoumeh Simbar; Ahmad Reza Baghestani (Tehran University of Medical Sciences, 2020)
Background & Aim: Some women, throughout their life cycle, experience unintended pregnancy and had to decide on continuing or terminating it. Although the decision-making process always recurs, few studies have so far shed light on this complex, and context-based process. The aim of the present study was to explore Iranian women's decision-making process to abort or continue an unintended pregnancy. Methods & Materials: This was a qualitative study using grounded theory approach. Data were collected through unstructured, in-depth interviews with 29 participants in Tabriz from March 2016 to May 2017. The participants were selected through the purposeful sampling method and data collection were continued until reaching data saturation. Data analysis was carried out concurrently with the data collection, using the MAXQDA software version 10. Results: Data analysis gave rise to four axial categories: "perceived threats", "resistance mixed with indecision", "values and supportive resources", as well as "acceptance and confirmation of decision". This means that the decision-making process among women with unintended pregnancy initially starts with a perceived threat as a main concern leading to their resistance towards accepting such a pregnancy, then exposure to threats arising from abortion can cause indecision and uncertainty in practicing abortion. In this respect, given the social support, women affected by religious values make efforts to choose the procedure with the least harm and threats and maximum acceptability and confirmability. "Confirmation of decision" is as well the outcome of the interactive process of decision-making. Conclusion: What can differentiate the theory of decision-making on abortion or continuation of an unintended pregnancy from the general theories of decision-making is its sociocultural confirmability. Social acceptance of abortion and childbearing in line with moral evaluation of fetal development directs the confirmability process of decision-making about unintended pregnancy.